Penglibatan dan peranan penduduk tempatan dalam penjenamaan tempat di Pulau Langkawi, Kedah - Nor Hidayah, Kamarudin (2019)
Place branding has been applied over the past decades as a marketing, in order to promote awareness among the locals. Malaysia has been promoting the place branding with the slogan “Malaysia Truly Asia” in an effort to attract foreign tourists. This study examines the involvement and role of residents and the use of social media in the branding process. Therefore, disclosure of “Naturally Langkawi” branding should be clearly communicated to the locals. So, they can engage themselves and play a role’s in place branding. Since, place branding is impossible without the participation of the locals in all stages. Therefore, place branding efforts have to integrate the locals in the island. This sudy used the Media Richness Theory. This study is conducted in Pulau Langkawi and it involved ten local residents, two officers from Langkawi Authority Development (LADA) and Community Cooperation of Kampung Kilim. The researcher utilised semi structure interview, visual methodology and online observation to explore the place branding. The data were analysis using thematic analysis. The results show that locals are still confused and less exposed to the “Naturally Langkawi” slogan. The results show that locals are still confused and less exposed to the “Naturally Langkawi” slogan. In addition, although locals play a role in the place branding process, their involvement is still minimal. Stakeholders such as tourists and people migrating to Pulau Langkawi are more involved in the branding process of the island. However, place branding is impossible without the participation of the locals in all stages. The aim of the development Pulau Langkawi is education tourism and Geopark tourism. So, locals involvement are not only for internal communication agents but also to educate tourists. Therefore, place branding efforts have to integrate the locals.